Evaluation of the impact of the Canadian CT head rule on British practice. Issue 4 (18th June 2004) - Boyle, A; Santarius, L; Maimaris, C
Abstract : Background: The Canadian CT head rule has been developed to identify which adults with minor head injuries require computed tomography (CT). This is hoped will reduce the number of CT scans performed for minor head injury in North America. It was unclear whether applying the rule would reduce or even increase the number of CT scans requested in UK emergency departments. Methods: A retrospective evaluation was conducted of all adults who presented after minor head injuries to Addenbrooke's emergency department. Clinical information about patients with head injuries is collected on standardised forms. A dataset was constructed to predict how many patients would require head CT scans if the Canadian CT rule was applied. Results: 1489 adults presented after minor head injury over a seven month period. Seventy four of these had CT scans for head injury, applying the Canadian CT head rule would have resulted in 132 CT scans being requested. This is significantly more (p>0.001). This would have resulted in a 68% increase in costs. Interpretation: The Canadian CT head rule would result in an increase in the number of CT scans requested for minor head injuries. This increased cost must be considered against the 488 skull radiographs that were requested during the study period.